Route to diagnosis of degenerative cervical myelopathy in a UK healthcare system: a retrospective cohort study. Issue 5 (5th May 2019) - Hilton, Bryn; Tempest-Mitchell, Jennifer; Davies, Benjamin; Kotter, Mark
Abstract : Objectives: Degenerative cervical myelopathy (DCM) presents insidiously, making initial diagnosis challenging. Surgery has been shown to prevent further disability but existing spinal cord damage may be permanent. Delays in surgery lead to increased disability and reduced postoperative improvements. Therefore, rapid surgical assessment is key to improving patient outcomes. Unfortunately, diagnosis of DCM in primary care is often delayed. This study aimed to characterise patients with DCM route to diagnosis and surgical assessment as well as to plot disease progression over time. Design: Retrospective, observational cohort study. Setting: Single, tertiary centre using additional clinical records from primary and secondary care centres. Participants: One year of cervical MRI scans conducted at a tertiary neurosciences centre (n=1123) were screened for cervical cord compression, a corresponding clinical diagnosis of myelopathy and sufficient clinical documentation to plot a route to diagnosis (n=43). Primary outcome measures: Time to diagnosis from symptom onset, route to diagnosis and disease progression were the primary outcome measures in this study. Disease severity was approximated using a prospectively validated method for inferring modified Japanese Orthopaedic Association (i-mJOA) functional scoring from clinical documentation. Results: Patients received a referral to secondary care 6.4±7.7 months after symptom onset. Cervical MRI scanning and neurosurgical review occurred 12.5±13.0 and 15.8±13.5 months after symptom onset, respectively. i-mJOA was 16.0±1.7 at primary care assessment and 14.8±2.5 at surgical assessment. 61.0% of patients were offered operations. For those who received surgery, time between onset and surgery was 22.1±13.2 months. Conclusions: Route to surgical assessment was heterogeneous and lengthy. Some patients deteriorated during this period. This study highlights the need for a streamlined pathway by which patients with cervical cord compression can receive timely assessment and treatment by a specialist. This would improve outcomes for patients using existing treatments.